Perilaku Konsumen Selama New Normal pada Fashion Busana Muslim Rumah Jahit Akhwat Makassar - Liong, Hasrulla; Angraeni, Isna (YUME : Journal of Management, 2021)
AbstractNew Normal are an essential source of information for decision-making for investors. The cash flow statement is part of the financial statements that are a significant concern for investors, one of which is used to measure a company's performance. In addition to cash flow, accounting profit is a report that measures the success of a company's operations for a certain period. This study aims to examine and examine the effect of operating cash flow and accounting profit on the level of stock returns. The statistical method used to test the hypothesis is multiple linear regression. The results showed that: partially operating cash flow and accounting profit affect the level of stock returns. Simultaneously, operating cash flow and accounting profit has a positive and significant effect on stock returns.Â Keywords: Operating Cash Flow, Accounting Profit, New Normal